PERAN KEPUASAN KONSUMEN MEMEDIASI PENGARUH MARKETING MIX TERHADAP NIAT BELI ULANG DEWATA KAOS DI DENPASAR - Maharani, Putu Susmithasen Sari Dewi; Jatra, I Made (E-Jurnal Manajemen; Vol 10 No 7 (2021)DO - 10.24843/EJMUNUD.2021.v10.i07.p01, 2021)
Trends Fashion that continue to evolve and turn, make companies need to implement an optimal marketing strategy. The marketing mix strategy is a basic tool in the form of a set of controlled variables used by companies to reach target markets. A customer satisfaction is very influential on company sales. Every company is required to understand and understand the right marketing strategy so that consumers feel satisfied and there is a repurchase intention so that it can increase sales to the company. This study aims to explain the role of consumer satisfaction in mediating the effect of the marketing mix on repurchase intention. This study uses primary data obtained by distributing questionnaires, offline (in person) and online (google form) to respondents Dewata Kaos consumers who live in Denpasar city with asample of 110 people, using a purposive sampling method. The analysis technique used is the Classical Assumption Test, Path Analysis and Sobel Test. The results showed that consumer satisfaction was able to mediate the effect of the marketing mix on repurchase intention of Dewata Kaos products in Denpasar. Keywords : Marketing mix, customer satisfaction, repurchase intention